The Effects of Acute Intracranial Pressure Changes on the Episcleral Venous Pressure, Retinal Vein Diameter and Intraocular Pressure in a Pig Model. (3rd April 2021) - Ghate, Deepta; Kedar, Sachin; Havens, Shane; Fan, Shan; Thorell, William; Nelson, Carl; Gu, Linxia; Tong, Junfei; Gulati, Vikas
ABSTRACT: Purpose: Orbital veins such as the retinal veins and episcleral veins drain into the cavernous sinus, an intracranial venous structure. We studied the effects of acute intracranial pressure (ICP) elevation on episcleral venous pressure, intraocular pressure and retinal vein diameter in an established non-survival pig model. Methods: In six adult female domestic pigs, we increased ICP in 5 mm Hg increments using saline infusion through a lumbar drain. We measured ICP (using parenchymal pressure monitor), intraocular pressure (using pneumatonometer), episcleral venous pressure (using venomanometer), retinal vein diameter (using OCT images) and arterial blood pressure at each stable ICP increment. The average baseline ICP was 5.4 mm Hg (range 1.5–9 mm Hg) and the maximum stable ICP ranged from 18 to 40 mm Hg. Linear mixed models with random intercepts were used to evaluate the effect of acute ICP increase on outcome variables. Results: With acute ICP elevation, we found loss of retinal venous pulsation and increased episcleral venous pressure, intraocular pressure and retinal vein pressure in all animals. Specifically, acute ICP increase was significantly associated with episcleral venous pressure (β = 0.31; 95% CI 0.14–0.48, p < .001), intraocular pressure (β = 0.37, 95%CI 0.24–0.50; p < .001) and retinal vein diameter (β = 11.29, 95%CI 1.57–21.00; p = .03) after controlling for the effects of arterial blood pressure. Conclusion: We believe that the ophthalmic effects of acute ICP elevation are mediated by increased intracranial venous pressure producing upstream pressure changes within the orbital and retinal veins. These results offer exciting possibilities for the development of non-invasive ophthalmic biomarkers to estimate acute ICP elevations following significant neuro-trauma.